Investigation of the certain internet domain statistical characteristics - Кириченко, Оксана Леонідівна; Остапов, Сергій Едуардович; Кановський, Ігор Яковлевич (Eastern-European Journal of Enterprise Technologies, 2014)
The review of works, in which statistical characteristics of complex networks were studied on the example of WWW-space, was conducted in the paper. For collecting and processing statistical information of web-pages, the software (crawler), which allowed to conduct network sounding from many entry points was designed and written. Segments net.ua, edu.ua of Ukrainian web-space and segment ac.il of Israeli web-space were investigated. Clusterness coefficients for these segments were calculated. It is shown that increasing the depth of sounding leads only to quantitative changes and qualitative network indicators remain almost unchanged. Probability plots of nodes in degrees on output and input connections and for undirected graphs of the studied segments of web-space are given. It was found that the subnets of input connections (in degree) demonstrate the power-series probability distribution of nodes with the initial section exponent (-2.2), indicating the scaleless nature of the graph. For the subnet of output connections (out degree) exponential probability distribution of the studied nodes, for which the average degree of nodes was calculated, was obtained. The considered zones do not contain significant features and their level fully corresponds to current trends of the Internet development. The comparison of the obtained results with literary data was conducted.